Demographic Structure of the 18th Century Ottoman Rule in the Balkans: A Study of Judicial Records (QÄdÄ« Sijil) in Manastir - Idriz, Mesut (IJISH (International Journal of Islamic Studies and Humanities), 2020)
Based on the Ottomans' archival materials, it has become incumbent upon the Ottoman or Balkan historian to investigate and analyze as objectively as possible the history of Ottoman rule in this region. Among all the Ottoman archives' documents, those of the judicial records (Shari’ah or Qadi Sijils) are considered to be the most important. In them, we have both a reliable objective source and a chronology of history concerning the Balkans and other regions. These records were not merely compilations of bureaucratic, administrative, and verbose data relating only to judicial, social, architectural, economic, and agricultural undertones. These facts are already explicitly stated in the Sijils themselves. It is, however, implicit facts which are of great importance and which are of enormous historical significance. The demographic structure is among the most complicated and disputed issues among the historians of religion and social sciences. Considering the objective data found in the Shari’ah Sijils, particularly to those about the most important district of the Ottomans in the Balkans, namely Manastir (today Bitola), the subject of demography will be analyzed as objectively as possible. Besides, in this article, both explicit and implicit facts will be studied.